Pengaruh Literasi Keuangan, Gaya Hidup, dan Cashback Terhadap Impulse Buying Mahasiswa Pengguna Shopee di Kota Malang - Zainal Abidin; Tin Agustina Karnawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to examine the influence of financial literacy, lifestyle, and cashback on impulse buying. This study uses a quantitative approach with multiple linear regression analysis methods. This study obtained data by administering questionnaires to 100 student respondents who use Shopee in Malang City. The data was then analyzed using the SPSS application. The results of this study indicate that financial literacy das no significant effect on impulse buying in student users of Shopee in Malang City, Lifestyle has no significant effect on impulse buying in student users of Shopee in Malang City, Cashback has a positive and significant effect on impulse buying in student users of Shopee in Malang City.